44.0k views
0 votes
Which of the following statements follows from (x - 3)2 = 7?

x2 + 9 = 7

x - 3 = ±

x - 3 = ±49

2 Answers

2 votes
the first one hope this clarifies
User Eliot Sykes
by
5.8k points
3 votes

Answer:

Option B is correct


x-3 = \pm √(7)

Explanation:

Given the equation:


(x-3)^2 = 7

taking square root both sides we have;


√((x-3)^2) = \pm √(7)

Using exponent rules:


\sqrt[n]{x^n}=x

then;


x-3 = \pm √(7)

Therefore, the following statements follows from
(x-3)^2 = 7 is,
x-3 = \pm √(7)

User Sam Zhou
by
5.5k points